The organisation of agricultural production in East Germany since World War II: Historical roots and present situation; Organisation der Agrarproduktion in Ostdeutschland seit dem 2. Weltkrieg: Historische Wurzeln und aktuelle Situation - Axel Wolz (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2013)
Up to the end of World War II, the political-economic framework had been relatively similar all over Germany. However, the farm structure was different. While in both parts, the West and the East, about 90 per cent of all farms cultivated less than 20 ha and about one per cent more than 100 ha, the large fams cultivated about 7 per cent of the agricultural area in the West, but about 30 per cent in the East. Following the unconditional surrender of Germany in 1945 and its division by the four Allies, the differences in the organisation of agricultural production between East and West became more pronounced. In the Soviet Occupation Zone and then with the creation of the German Democratic Republic in October 1949, the socialist model of agricultural production was introduced in three phases: (1) an enforced land reform between 1945-49; (2) the repression of farmers cultivating more than 20 ha, starting in 1949, and finally (3) the collectivization of agricultural production starting in 1952 and finalised in the Socialist Spring in April 1960. While socialist agriculture had been built up on blood and tears, it came to be fully accepted by the East German population over time and heavily defended also by those political forces which pushed for a regime change in 1989. With the collapse of the socialist regime in 1989 and German reunification in 1990, socialist agriculture had to be transformed into a system compatible with pluralistic democracy and market economy. Similarly, those whose assets had been confiscated were supposed to be restituted. However, the legal system at reunification differentiated between those who were expropriated either before 1945 or after 1949 and those between 1945 and 1949 under Soviet occupation. While the first group was entitled to restitution, the latter group received little compensation. At the time of transition, most politicians and agricultural economists assumed that family farming would re-emerge in the East and the modes of agricultural production would adjust between the two parts. However, even more than two decades after reunification, German agriculture is characterized by two distinguished different agricultural production systems. While West German agriculture continued the tradition of small-scale family farms relying on family labour, East German agriculture is characterised by large-scale corporate farms relying on permanently employed labour. In this way, German agriculture can be characterised as One country - Two systems. – – Bis zum Ende des 2. Weltkriegs waren die politischen Rahmen in ganz Deutschland einheitlich. Allerdings gab es Unterschiede in der Organisation der landwirtschaftlichen Produktion zwischen dem westlichen und östlichen Teil. Zwar umfassten in beiden Teilen ca. 90 Prozent der Betriebe weniger als 20 ha und ca. ein Prozent mehr als 100 ha, doch bewirtschafteten die größten Betriebe im Westen ca. sieben Prozent der landwirtschaftlichen Nutzfläche, im Osten jedoch ca. 30 Prozent. In Folge der bedingungslosen Kapitulation Deutschlands sowie der Aufteilung in vier Besatzungszonen wurden diese Unterschiede in den folgenden Jahrzehnten weiter verstärkt. In der Sowjetischen Besatzungszone und später der Deutschen Demokratischen Republik wurde in drei Phasen ein sozialistisches Modell der landwirtschaftlichen Produktion geschaffen: (1) entschädigungslose Enteignung von Gutsbesitzern und Nazi-Kollaborateuren im Zuge der Bodenreform von 1945 bis 1949; (2) Beseitigung des Groß- und Mittelbauerntums ab 1949; sowie (3) Kollektivierung durch Bildung von Landwirtschaftlichen Produktionsgenossenschaften ab 1952, die mit dem Sozialistischen Frühling im April 1960 abgeschlossen war. Die sozialistische Landwirtschaft wurde mit Blut und Tränen aufgebaut. Im Laufe der Jahre wurde sie jedoch von der Bevölkerung völlig akzeptiert. So wurde sie nach 1989 auch von jenen politischen Gruppen verteidigt, die auf einen Sturz des Regimes hingearbeitet hatten. Nach dem Zusammenbruch des sozialistischen Regimes musste auch die Landwirtschaft nach marktwirtschaftlich konformen Prinzipien organisiert werden. Die zwangsenteigneten Betriebsmittel und Vermögen mussten an ihre ursprünglichen Besitzer zurückgegeben bzw. privatisiert werden. Allerdings wurde juristisch zwei Gruppen unterschieden: (1) diejenigen, die entweder vor 1945 sowie nach 1949 enteignet wurden und (2) diejenigen, die zwischen 1945 und 1949 während der sowjetischen Besatzung enteignet wurden. Während die erste Gruppe einen Rechtsanspruch auf Rückgabe des Vermögens hatte, gab es für die zweite nur einen auf eine relativ geringe Entschädigung. Die meisten Politiker und Agrarökonomen gingen in der Anfangsphase der Transformation davon aus, dass sich in Ostdeutschland schnell Familienbetriebe entwickeln und somit die Organisation der landwirtschaftlichen Produktion in beiden Teilen Deutschlands angleichen würde. Mehr als zwei Jahrzehnte nach der Wiedervereinigung ist die Landwirtschaft jedoch in zwei unterschiedlichen Systemen organisiert. In Westdeutschland dominieren weiterhin kleinstrukturierte Familienbetriebe. In Ostdeutschland herrschen großstrukturierte Betriebe vor, die als juristische Personen registriert sind und primär festangestellte Arbeitskräfte beschäftigen. In diesem Sinne kann man die Landwirtschaft in Deutschland als Ein Land - Zwei Systeme beschreiben.
urn:nbn:de:gbv:3:2-27321
Keywords: N54; P32; Q1; 330; organisation of agricultural production; Soviet Occupation Zone; German Democratic Republic; reunification; Germany; Organisation der Agrarproduktion; Sowjetische Besatzungszone; Deutsche Demokratische Republik; Wiedervereinigung; Deutschland